A Preliminary Investigation of the Effects of Discrete Virtual Rotation on Cybersickness - Ryge, Andreas N.; Vollmers, Casper; Hvass, Jonatan S.; Andersen, Lars K.; Berthelsen, Theis; Bruun-Pedersen, Jon R.; Nilsson, Niels C.; Nordahl, Rolf (2018 IEEE Conference on Virtual Reality and 3D User Interfaces (VR), 2018)
Most virtual reality (VR) applications require the user to travel through the virtual environment (VE). However, some users are susceptible to cybersickness, and this issue is particularly prominent if the user is physically stationary while virtually moving. One approach to minimizing cybersickness is to rotate the user in discrete steps. This poster presents a between-subjects study (n=42) comparing this approach to smooth virtual rotation. The results revealed a statistically significant increase in self-reported sickness after exposure to the VE in case of both conditions. No statistically significant differences between the two conditions were found.